Increased Cerebrospinal Fluid Uric Acid Levels in Guillain–Barré Syndrome - Chang, Sheng-Hui; Tian, Xiao-Bing; Wang, Jing; Liu, Ming-Qi; Huang, Chen-Na; Qi, Yuan; Zhang, Lin-Jie; Gao, Chun-Li; Zhang, Da-Qi; Sun, Li-Sha; Yang, Li (Frontiers in Neurology, 2020)
Uric acid (UA) is a natural scavenger for peroxynitrite and can reflect antioxidant activity and oxidative stress in several neurological disorders. Changes in serum and CSF levels of UA have been reported in patients with multiple sclerosis and neuromyelitis optica spectrum disorders. The levels of UA in cerebrospinal fluid (CSF) are relatively poorly understood in patients with Guillain-Barré syndrome (GBS). It remains unclear whether UA can play an antioxidant role and reflect oxidative stress in GBS. The purpose of this study is to investigate CSF and serum UA levels in patients with GBS and their relationship with clinical characteristics. The CSF and serum UA levels were detected in 43 patients with GBS, including 14 acute inﬂammatory demyelinating polyneuropathy (AIDP), 6 acute motor axonal neuropathy (AMAN) and 13 with acute motor and sensory axonal neuropathy (AMSAN), 7 Miller Fisher syndrome (MFS), and 3 unclassified, and 25 patients with non-inflammatory neurological disorders (NIND) as controls. Moreover, serum UA levels were also detected in 30 healthy controls. The levels of UA were measured using uricase based methods by automatic biochemical analyzer. CSF UA levels were significantly increased in patients with GBS (p = 0.011), particularly in patients with AIDP (p = 0.004) when compared with NIND. Among patients with GBS, CSF UA levels were higher in those with demyelination (p = 0.022), though the difference was not significant after multiple testing correction. CSF UA levels in GBS were positively correlated with serum UA levels (r = 0.455, p = 0.022) and CSF lactate (r = 0.499, p = 0.011). However, no significant correlations were found between CSF UA levels and GBS disability scores. There were no significant differences in serum UA levels among GBS, NIND and healthy controls. These results suggest that CSF UA may be related to the pathogenesis of demyelination in patients with GBS, and may be partially determined by serum UA and the impaired blood-nerve barrier.